Risk Management, Governance and Financing Issues in Public-Private Partnership Transportation Projects - Mandiartha, Putu; Intan Suhana, Mohd Razelan; Azlina, Ismail (Penerbit Universiti Malaysia Pahang, 2017)
This paper discusses issues related to risk management, governance, and financing of public-private partnerships transportation projects. The allocation of risks and the requirements for ownership and equity provision were examined through analysis of a range of contracts. Lessons learnt from a series of Australia’s public-private partnerships transportation projects are also presented. The results showed that from the perspective of risk allocation, the arrangements were consistent among the projects. Some fluctuations, however, were observed in terms of equity provision. Initially, the contracts were developed based on the private sector taking full traffic demand risk and promising outcomes led to revenue sharing clauses being introduced. Consequently, overoptimistic demand forecasts resulted in the market rejecting the acceptance of traffic demand risk. The paper also presents the variation between the case study projects in terms of excess revenue sharing. The analysis also suggests that, in arranging these types of projects, traffic demand issue would be prominent and should be given major concern since it would be closely related with the revenue of the projects, which in turn would affect the equity of the projects.